Refractive Index and Thermo‐Optic Coefficients of Ge‐As‐Se Chalcogenide Glasses. (5th April 2016) - Gleason, Benn; Richardson, Kathleen; Sisken, Laura; Smith, Charmayne
Abstract : Seventeen glasses in the Ge‐As‐Se ternary glass‐forming region have been fabricated and analyzed to provide input for optical design data and to establish composition‐ and structure‐based relationships to aide development of novel chalcogenide glasses with tailored optical functionality. While known that Ge addition to binary As‐Se glasses enhances the mean coordination number (MCN) of the network and results in increased T g and decreased CTE, this work highlights the impact on optical properties, specifically mid‐wave (λ = 4.515 μm) index and thermo‐optic coefficient (d n /d T ). Trends in property changes were correlated with an excess or deficiency of chalcogen content in the glassy network as compared to stoichiometric compositions. Transitions in key optical properties were observed with the disappearance of Se–Se homopolar bonds and creation of As–As homopolar bonds which are associated with the Se‐rich and Se‐deficient regions near the stoichiometry, respectively. A second transition was observed with the creation of GeSe ethane‐like structures, which are only present in strongly Se‐deficient networks. Fitting d n /d T values with a simplified version of the thermal Lorentz–Lorenz formulation yielded a linear relation between the quantity ( n −3 ∙d n /d T ) and the CTE, which can be used to predict compositions with the near‐zero d n /d T required for athermal optical systems.